The Hara Museum of Contemporary Art. - Hara Museum of Contemporary Art, Tokyo (Tokyo : Hara Museum of Contemporary Art, 1985)
Paik, Nam June ; Shiraga, Kazuo ; Motonaga, Sadamasa ; Shinohara, Ushio ; Lee U-Fan ; Miki, Tomio ; Rauschenberg, Robert ; Klasen, Peter ; Klein, Yves ; Onosato, Toshinobu ; Wols ; Noland, Kenneth ; etc.
Engels & Japans
boek